2007
DOI: 10.1590/s0034-89102007000800009
|View full text |Cite
|
Sign up to set email alerts
|

Vacina BCG contra tuberculose: efeito protetor e políticas de vacinação

Abstract: OBJECTIVE:The BCG vaccine has been in use since 1921, but still arouses controversy and uncertainties. The objective was to analyze the protective effect of the BCG vaccine in its fi rst and second doses and the accompanying vaccination policies. METHODS:A systematic review of the literature in both English and Spanish was carried out, covering the period 1948 to 2006, using the PubMed database. The main search terms used included BCG vaccine, BCG effi cacy, BCG and tuberculosis. The studies were grouped by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 31 publications
1
13
0
13
Order By: Relevance
“…In the municipality of Rondonópolis-MT, of 134 tuberculosis patients, 47% were between 35 and 54 years old [19]. Moreover, it was observed that in Natal-RN, there is a low prevalence of individuals with tuberculosis for both genders up to 14 years of age, which may be related to the temporary immunity granted by BCG vaccine [20]. The educational level of tuberculosis patients can be observed below (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the municipality of Rondonópolis-MT, of 134 tuberculosis patients, 47% were between 35 and 54 years old [19]. Moreover, it was observed that in Natal-RN, there is a low prevalence of individuals with tuberculosis for both genders up to 14 years of age, which may be related to the temporary immunity granted by BCG vaccine [20]. The educational level of tuberculosis patients can be observed below (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there were studies that only focused on the prevalence or incidence of health problem events (I) (12)(13)27,32,45,(47)(48)67,81,(83)(84)(85)(86)90,92) ; others to iden fy and/or associate risk factors (II) ( ; and s ll others to correlate interven ons with preven on, prophylaxis or reduc on of events (III) (14)(15)(17)(18)20,23,33,46,(50)(51)(53)(54)(55)58,62,(64)(65)(68)(69)(70)(71)(72)(73)(74)(75)(76)(79)(80)82,89,91,(93)(94) .…”
Section: Discussionmentioning
confidence: 99%
“…É importante ressaltar que não existem evidências para a 2ª dose da BCG, suspensa pelo Ministério da Saúde em 2006 2 . Vários estudos sobre revacinação BCG não mostraram proteção conferida pela segunda dose da vacina nos adolescentes e profissionais de saúde [22][23][24] . O estudo não mostrou associação entre a TT positivo e contato com paciente com TB se contrapondo aos dados encontrados em outras pesquisas 8,14 .…”
Section: Discussionunclassified